Correlation of apparent diffusion coefficient measured by diffusion‐weighted MRI and clinicopathologic features in pancreatic cancer patients. Issue 2 (February 2013) - Hayano, Koichi; Miura, Fumihiko; Amano, Hodaka; Toyota, Naoyuki; Wada, Keita; Kato, Kenichiro; Sano, Keiji; Takeshita, Koji; Aoyagi, Tomoyoshi; Shuto, Kiyohiko; Matsubara, Hisahiro; Asano, Takehide; et al.
Abstract Background/purpose The aim of this study was to evaluate the clinical usefulness of diffusion‐weighted magnetic resonance imaging (DWI) in patients with pancreatic cancer by comparing the apparent diffusion coefficient (ADC) value with clinicopathologic features. Methods Twenty‐two consecutive patients (12 men, 10 women; mean age 64.4 years) with pancreatic cancer underwent DWI before surgery. We retrospectively investigated the correlations between tumor ADC value and clinicopathologic features. Results Apparent diffusion coefficient value was significantly lower for pancreatic cancer than for noncancerous tissue (P < 0.001). Receiver operating characteristic analysis yielded an optimal ADC cutoff value of 1.21 × 10−3 mm2/s to distinguish pancreatic cancer from noncancerous tissue. There was a significant negative correlation between ADC value and tumor size (r = ‐0.59, P = 0.004) and between ADC value and number of metastatic lymph nodes (r = ‐0.56, P = 0.007). Tumors with low ADC value had a significant tendency to show high portal venous system invasion (P = 0.02) and extrapancreatic nerve plexus invasion (P = 0.01). Conclusions Apparent diffusion coefficient value appears to be a promising parameter for detecting pancreatic cancer and evaluating the degree of malignancy of pancreatic cancer.